Essential outsiders : Chinese and Jews in the modern transformation of Southeast Asia and Central Europe - Chirot, Daniel; Reid, Anthony, 1939- (Jackson School publications in international studies., 1997)
The essays in this book explore the reasons why the Jews in Central Europe and the Chinese in Southeast Asia have been both successful and stigmatized, essential but not fully accepted. They offer insights into the very formation of ethnic and national identities in the modern world and ideas about when the process is more or less likely to lead to either violent social separation and conflict or peaceful accommodation. Their careful scholarship and measured tone contribute to a balanced view of the subject and introduce a historical depth and comparative perspective that have generally been lacking in past discussions. Those who want to understand both contemporary Southeast Asia and the legacy of the Jewish experience in Central Europe will gain new insights from the book.